Covid Conversations 1: Peter Sellars. (February 2021) - Sellars, Peter; Shevtsova, Maria
Abstract : In this profoundly dialogical exchange, Peter Sellars, theatre director, researcher, and teacher, and Maria Shevtsova open out a whole array of questions on the integral relation between politics and the theatre in its multiple manifestations. These questions not only concern the damages inflicted by the present Covid-19 pandemic but also those developed by the neoliberal economics and politics of the past forty years and more. In Sellars's view, neoliberalism has been the hotbed of social injustices, inequities, market and other forms of current enslavement, migrations, refugee and related precarities, and the havoc of the world climate in which the plight of humanity and that of the planet are indelibly interconnected. His and Shevtsova's discussion links such vital concerns with his theatre practice, which ranges from his engagement with local communities and indigenous peoples – he details some of his work with the collective, community organization of two Los Angeles Festivals of the early 1990s – to the various forms of his music theatre in which he collaborates, in institutional structures, with highly proficient musicians, singers and dancers. The focus chosen here from his music theatre is The Indian Queen (2013), which Sellars dramaturgically invents using pieces by Henry Purcell combined with prose fragments by Nicaraguan novelist Rosario Aguilar. Peter Sellars is an internationally renowned theatre director among whose more recent productions is Mozart's Idomeneo, premiered at the Salzburg Festival in 2019. Maria Shevtsova, Professor of Drama and Theatre Arts at Goldsmiths, University of London, is editor of New Theatre Quarterly. This conversation took place on 16 August 2020, was transcribed from the recording by Kunsang Kelden, and was edited by Maria Shevtsova.